Geographical perspective on the relationship of the green economy to sustainable development - Abdullah, Saif Shehab Ahmed; Abdal, Ayad Abdel-Reda (Al-Adab Journal, 2022)
This research deals with the relationship between each of the green economy and sustainable development, the relationship between them is a close and intertwined relationship until the green economy for sustainable development for sustainable development through the application of the green economy as one of its mechanisms.The views that were taken in the study that link development and the green economy, as an economic approach or as a development approach, have varied, and here highlights another aspect of this relationship, which is the point of view of the point of view of the geographical approaches to the concept of green economy from the point of view of environmental geography and development sustainable, sustainable development, sustainable development, sustainable development, sustainable development.